Number of Langerhans cells is decreased in premalignant keratosis and skin cancers - Shevchuk, Z.; Filip, A.; Shevchuk, V.; Kashuba, E. (Experimental Oncology, 2014)
Background: It was shown earlier that a number of CD207 positive Langerhans cells was lower in basal cell carcinomas than in the normal epidermis. Moreover, benign skin lesions presented a higher number of Langerhans cells when they were compared to malignant tumors. Aim: To count Langerhans cells, assessing expression levels of CD1A and CD207 markers in actinic keratosis, basal and squamous cell carcinomas, compared with the normal skin. Comparison of Langerhans cells might give a valuable prognostic marker for skin cancer. Methods: Immunohistochemistry and methods of statistics were used. Results: Expression of CD1A and CD207 markers was assessed in tumor samples of actinic keratosis, cutaneous basal and squamous cell carcinomas, in comparison with the normal skin. In each cohort there were 40 patients (and 11 healthy individuals). We have shown that the number of Langerhans cells is considerably lower in cutaneous basal and squamous cell carcinomas, compared with their number in the normal skin (p < 0.0001). Conclusions: CD1A expression correlated with CD207 expression only in the control group. There was no correlation in actinic keratosis, basal and squamous cell carcinoma. This may suggest an alteration of Langerhans cells phenotype in skin neoplastic diseases, making the number of Langerhans cells a valuable prognostic factor for skin tumors. Key Words: Langerhans cell, CD207, CD1A, actinic keratosis, skin cancer.